PENGARUH KEPUASAN WAJIB PAJAK ATAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK (Survei Pada Kantor Pelayanan Pajak Kota Bogor) - Patar Simamora (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2018)
ABSTRACTLow tax compliance is a matter of serious concern inmany developing countries. The success of the self assessmentsystem, depend on high and low of consciousness of people to tax.If level of tax compliance in one state is relative low, the first it isdone by government is looking for solution why it happens. Tolooking for of the root problem which the better than incite thepressing a claim but not equal with satisfaction for servicing. Theservicing is not done with careless because it will form the badimage, and at the last will inflicted a loss upon the government ifthe image will form tax-phobia. The people as the taxpayersreserve the right, quickly service, clear, and satisfied. Dimension ofservice quality are reliability, responsiveness, assurances,empathy, and tangibles. Raising the service quality must docontinuous to keep the taxpayers satisfaction. Thus, in Bogor ofTax Office Service, as the public service office has directrelationship with the taxpayers are not apart from the serviceproblem. This research has goals to description the level oftaxpayers satisfaction will be able to pay their obligation ismeasured from service quality dimension and identificationinfluence of taxpayers satisfaction on services to taxpayerscompliance.Key words: taxpayers satisfaction, service quality, taxpayerscompliance.